Correlation between the corrosion resistance and the hardness scattering of structural metals treated with a pulsed electric current - Babutsky, Anatoly (Materiali in tehnologije, 2010)
The results of corrosion tests of two kinds of structural metals initially treated by a pulsed electric current of high density are presented. According to the data obtained, the treatment influences the corrosion of metals. There is a correlation between the corrosion test results and the hardness scattering of the metals.
Keywords: korozija; trdota; pulzirajoči tok; kovine